Galectin-Carbohydrate Interactions in Biomedicine and Biotechnology - Laaf, Dominic; Bojarová, Pavla; Elling, Lothar; Křen, Vladimír (Trends in biotechnology, 2019)
Cellular communication events are mediated by interactions between cell-surface sugars and lectins, which are carbohydrate-binding proteins. Galectins are β-galactosyl-binding lectins that bridge molecules by their sugar moieties, forming a signaling and adhesion network. Severe changes in glycosylation and galectin expression accompany major processes in oncogenesis, cardiovascular disorders, and other pathologies, making galectins attractive therapeutic targets. Here we discuss advanced strategies of chemo-enzymatic carbohydrate synthesis for creating lead glycomimetics and (neo-)glycoconjugates for galectin-1 and -3 targeting in biomedicine and biotechnology. We will describe the challenges and bottlenecks on the route into biomedical and biotechnological practice and present the first clinical candidates. The coming era will see an exciting translation of selective well-defined high-affinity galectin ligands from bench to bedside.
Keywords: Protein Binding; Biological Therapy; cílená molekulární terapie; biologická terapie; glycomimetic; biotechnologie; Biomedical Research; Cancer; neo-glycoprotein; glycoconjugate; Galectins; galectin; vazba proteinů; biomedicínský výzkum; thiodigalactoside; Biotechnology; metabolismus sacharidů; Molecular Targeted Therapy; galektiny; Carbohydrate Metabolism